In vitro effect of the hydroalcoholic and ethanolic extracts of papaya seeds (Carica papaya) against Haemonchus contortus - Marroquín-Tun, María de los Ángeles; Higuera-Piedrahita, Rosa Isabel; López-Arellano, María Eugenia; López-Arellano, Raquel; de la Cruz-Cruz, Héctor Alejandro; Silva-Mendoza, Rocío; Cuéllar-Ordaz, Jorge Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Among the main health problems for sheep production are gastrointestinal parasites, of which the most important nematode is Haemonchus contortus. Current control strategies focus on the effectiveness, along with the low impact on the ecosystem. The study of the integral control of parasites allows the investigation of alternatives with probable anthelmintic effect, such as the use of papaya (Carica papaya) seeds. This study aimed at evaluating the in vitro effect of hydroalcoholic and ethanolic extracts of papaya seeds on eggs and larvae of H. contortus. The study was carried out with the equipment and facilities of Laboratory 3 of the Multidisciplinary Research Unit at the Facultad de Estudios Superiores Cuautitlán, UNAM. The extracts were prepared through maceration in solvent. A sheep was inoculated with 5000 L3 of H. contortus, a strain isolated and maintained in the facilities. Fecal samples were collected, and eggs were recovered for the hatch inhibition assay. The eggs and L3 were pretreated with hydroalcoholic and ethanolic extract of papaya seed (2.5 mg/ml), distilled water, ethanol 90 %, and levamisole (7.5 mg/ml). The abomasal explants technique was used to evaluate the effect of the extracts on L3 and its association to the abomasal mucosa. An ANOVA was performed for repeated samples using the Statgraphics program. The ethanolic extract of the papaya seed inhibited 92 % of hatching, and the hydroalcoholic extract 50 % (p <0.05). In the case of the explants, the ethanolic extract showed 10 % of the larvae not associated with the abomasal tissue, followed by the hydroalcoholic extract with 60 % of non-associated larvae (p<0.05). In conclusion, the ethanolic extract has an effect on eggs, while the hydroalcoholic extract inhibits the association to the abomasal tissue.